PENGARUH KUALITAS WEBSITE PERPUSTAKAAN TERHADAP KEMUDAHAN PENGGUNA DI POLTEKKES KEMENKES PONTIANAK - Nur Asila Khairunnisa; Atiqa Nur Latifa Hanum; Sahidi Sahidi (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
Thisl study aims to determinel the quality ofl the library website, the level of ease of library website users and to determine the effect of the quality of the library website on the ease of users at the Poltekkes Kemenkes Pontianak. The method used quantitative approach. The population is all active students of Poltekkes Kemenkes Pontianak which amounts to 568 people. The sample was determined using the Slovin formula which yielded 85 respondents. Data collection methods through documentation and questionnaires. Data measurement in this study used Likert scale. The validity test used Pearson Correlation while the reliability test used Alpha Cronbach with 30 samples. The datal analysis techniquel uses thel mean formulal followed byl the grandl mean formulalof the whole laverage. Test the hypothesis using a simple linear regression test and a correlation test using the product moment. The quality of the website produces a value of 4.01 which is at a good level while the ease of users produces 4.40 which is at a very easy level which shows that the quality of the library website has a positive and significant effect on the ease of users of the Poltekkes Library website of the Ministry of Health Pontianak.